Strategi Kebijakan Penyaluran ZIS Produktif Untuk Pemberdayaan Usaha Mikro Kecil dan Menengah di Provinsi Bengkulu - Jambak, Desrizaldi (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy paper explains that Bengkulu Province has great potential in developing Micro, Small, and Medium Enterprises (UMKM), but still faces various challenges, such as limited capital and management capacity. On the other hand, the potential for collecting Zakat, Infak, and Sedekah (ZIS) funds in Bengkulu is also quite large. Therefore, the distribution of productive ZIS can be a strategic solution to empower UMKM and encourage regional economic growth. This article aims to analyze the potential and challenges of distributing productive ZIS for empowering UMKM in Bengkulu Province, formulate effective policy strategies, and provide recommendations for policy implementation. This paper uses a qualitative method with a descriptive analysis approach and SWOT (Strengths, Weaknesses, Opportunities, Threats). Data were obtained through in-depth interviews with stakeholders, including ZIS institution managers, UMKM actors, local government representatives, and experts in the field of sharia economics to explore information on the potential and challenges of distributing productive ZIS, UMKM needs, and perceptions and expectations related to effective policy strategies. The results show that the potential for collecting and distributing ZIS funds in Bengkulu has not been optimally utilized. The distribution of ZIS funds is still dominated by consumptive activities, whereas the distribution of productive ZIS can provide a greater and more sustainable impact on UMKM. Therefore, an effective policy strategy is needed to increase the distribution of productive ZIS, including distribution models, monitoring mechanisms, and synergy with local government programs and other financial institutions.